Inward Investment, Employment and Government Policies in Wales. Issue 8 (2nd August 2016) - Cook, Mark; Fallon, Grahame
Abstract : Cook M. and Fallon G. Inward investment, employment and government policies in Wales, Regional Studies . This empirical paper examines the links between multinational enterprises' countries of origin, types of inbound foreign direct investment (IFDI), related capital investment levels and the resultant effects on regional employment in Wales, a peripheral region of the UK. Longitudinal, official data are used to examine the relationships between these variables, making use of statistical techniques. The findings are used to make recommendations for inward investment policy development in Wales, focusing on the targeting of IFDI from those countries of origin whose multinational enterprises appear likely to contribute most to the future creation and safeguarding of regional employment.